Case Analysis: FGV Holdings Berhad - Nur Haziqah Fathiah binti Muhamed Noor; Abdul Razak Bin Abdul Hadi (Ekonomi dan Bisnis, 2021)
This empirical study is pursued with the objective to examine the evolution of FELDA since its establishment in 1956 until the listing of its investment holding company, FGV Holdings Berhad, at Bursa Malaysia in 2012. Due to the poor financial performance of FGV, Felda has no choice but to take it out from Bursa Malaysia. From the literature review, the FGV company is one of the biggest producers of crude palm oil (CPO) in the world, contributing about 15% of Malaysia’s total annual production of CPO over the past ten years. FGV company operates in 9 countries throughout Asia, the Middle East, North America and Europe. Backed by a powerful workforce of more than 45,000 employees, FGV is indeed a multinational company. The main business focus of FGV has been on three key industry sectors - plantation, sugar, and logistics. FGV Holdings Berhad holds one important vision which is “To be among the world’s leading, integrated and sustainable agribusiness that delivers value to customers and stakeholders especially the smallholders”. However, the poor performance of FGV over the past five years has raised some concerns among its shareholders and stakeholders.  FGV is supposed to focus on creating value through human capital development, the embodiment of governance and compliance, building an integrated value chain advantage, and lastly cultivating diversification in commodities and geography. Overall, Felda understands the importance of FGV in nation building and this major shareholder is very concerned about value of partnership, integrity, dynamism, and sustainability because these are the critical factors for entrepreneurial success in the long run.